The Use Of Slang Language Style On Social Media Instagram By Gen-Z (Generation Z) - Syaputra, Ary Rahmad; Sari, Sapta; Endang, Anis (Social Sciences Journal, 2024)
Along with the times, advances in communication and information technology also have an impact on the cultural aspects of society, especially on the use of social media by Generation Z - a generation born in the era of information technology. The development of social media has led to the emergence of a new language style, which is often referred to as "slang" or "slang" language style. The role of social media in the spread of Slang is to Investigate how social media plays an important role in the spread and adoption of Slang styles among users by considering features such as user interaction, hashtag use, and content sharing capabilities. The social media platform Instagram served as the specific environment for this study, including features of the platform that are relevant to the use of Slang and users' communication behavior. The results of the above research show that the use of slang language styles among generation Z on Instagram social media has become a common phenomenon. This is in line with the characteristics of generation Z, which is known as a generation that is familiar with digital technology and social media